Association between lower geriatric nutritional risk index and low cognitive functions in United States older adults: a cross-sectional study - Liu, Jiuling; Oorloff, Melysze Deanne; Nadella, Adithya; Zhou, Ning; Ye, Min; Tang, Yifeng; Wang, Yuanwei (Frontiers in Nutrition, 2024)
Background We aimed to explore the association between the Geriatric Nutritional Risk Index (GNRI) and the risk of low cognitive functions among older adults in the United States (US).Utilizing data from the National Health and Nutrition Examination Study (NHANES) database, a cross-sectional analysis was conducted. The GNRI served as a tool for evaluating the nutritional status of participants, who were categorized into two groups based on their initial GNRI scores: those with scores > 98 indicating normal nutrition, and those with scores ≤ 98 indicating malnutrition. Cognitive function was assessed using the Consortium to Establish a Registry for Alzheimer's Disease word list learning test (CERAD W-L), the Digit Symbol Substitution Test (DSST), the Animal Fluency Test (AFT), and the composite-z score which was calculated by summing the z scores of individual tests, respectively. Weighted multiple logistic regression models were used to evaluate the association between GNRI and cognitive function. Interaction and stratified analyses were conducted.Results Among a sample of 2925 individuals aged 60 years or older, 51.3% were women. Among these individuals, 233 were identified as malnourished. Weighted multivariate logistic regression analyses indicated that individuals with malnutrition had an increased risk of low cognitive function, as evidenced by lower CERAD W-L scores (OR:1.68, 95%CI 1.19-2.36, p = 0.003), AFT scores (OR:1.74, 95%CI 1.26-2.41, p = 0.009), DSST scores (OR:1.63, 95%CI 1.11-2.38, p = 0.012), or composite z-scores (OR:1.87, 95%CI 1.29-2.71, p = 0.001). According to the variables evaluated, the interaction effects between low GNRI level and the elderly and stroke in specific cognitive domains were significant (P interaction <0.05).Conclusion: Lower GNRI level is associated with significantly low cognitive function among older adults, particularly among those who have experienced a stroke or the elderly (aged 70 years and older) population.